2009
DOI: 10.1002/rmv.613
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the BK polyomavirus: epidemiological, anthropological and clinical implications

Abstract: BK polyomavirus (BKV) is essentially ubiquitous in all human populations worldwide. Asymptomatic infection with this virus occurs during early childhood, leading to life-long persistence in the kidney. BKV has four subtypes that can be identified using serological and genotyping methods. The evolutionary aspects of BKV have remained poorly understood due to the limited availability of BKV genomes, since urinary excretion of BKV DNA is detected primarily in immunocompromised individuals. However, we have found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 84 publications
2
40
2
1
Order By: Relevance
“…The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig. 2) is about 20-fold higher than prior PCR-based prevalence estimates (17,25). A recent report by Chehadeh and Nampoory may also illustrate the problem of older BKV-I-biased PCR results (41).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig. 2) is about 20-fold higher than prior PCR-based prevalence estimates (17,25). A recent report by Chehadeh and Nampoory may also illustrate the problem of older BKV-I-biased PCR results (41).…”
Section: Discussionsupporting
confidence: 89%
“…PCR-based prevalence studies have suggested that infection with BKV-II or -III is rare in all human populations worldwide (17,25). In contrast to these prior PCR-based prevalence studies, our serological analysis indicates that 33/48 (69%) members of this group of subjects are BKV-II seropositive (defined by EC 50 titers of 100 or greater).…”
Section: Resultscontrasting
confidence: 76%
“…BKV isolates can be grouped into four genetically distinct subspecies (genotypes) [20][22]. While chronic infection with BKV genotype I (BKV-I) is believed to be common almost to the point of ubiquity in all human populations worldwide, PCR-based studies suggest that BKV genotypes II, III, and IV only infect a minority of adults.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is limited knowledge with regard to how these DNA viruses evolve. For BKPyV, different subtypes of viral genomes have been demonstrated to evolve from distinct human populations, with the archetypal variants being the dominant circulating virus (10). The host cell factors that contribute to the molecular evolution of PyVs remain to be determined.…”
mentioning
confidence: 99%